2016
DOI: 10.1016/j.soard.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent weight history and adult cognition: before and after bariatric surgery

Abstract: Background Cognitive deficits occur in a subset of individuals with obesity. Deficits can be reversed with bariatric surgery, though cognitive recovery is not equally exhibited across patients. Recent work shows obesity during adolescence portends medical complications in adulthood; it is unknown if obesity in adolescence predicts adult cognition or cognitive recovery following weight loss surgery. Objectives The current study examines the relationship between weight history and cognitive function in obese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The current evidence is also limited on the impact of mediating factors. None of the included longitudinal studies evaluated the mediating effects of sleep deprivation, physical activity levels, type of physical activity, diet/nutritional status and co-morbidities, despite the literature suggesting an important role of these factors in the causal pathway between childhood obesity and academic achievement [ 12 , 13 , 15 17 , 83 ]. However, most recently (after our literature search was performed), new findings were published on the link between meeting lifestyle-behaviour recommendations at age 11 years and academic achievement at age 12 years ( n = 4253).…”
Section: Discussionmentioning
confidence: 99%
“…The current evidence is also limited on the impact of mediating factors. None of the included longitudinal studies evaluated the mediating effects of sleep deprivation, physical activity levels, type of physical activity, diet/nutritional status and co-morbidities, despite the literature suggesting an important role of these factors in the causal pathway between childhood obesity and academic achievement [ 12 , 13 , 15 17 , 83 ]. However, most recently (after our literature search was performed), new findings were published on the link between meeting lifestyle-behaviour recommendations at age 11 years and academic achievement at age 12 years ( n = 4253).…”
Section: Discussionmentioning
confidence: 99%
“…A study from the USA in adults undergoing bariatric surgery showed less recovery of attention in participants who had had obesity during adolescence, and it was suggested that cognitive alterations associated with early onset obesity are less responsive to weight loss in comparison to those related to obesity with adulthood onset. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of childhood obesity on educational level may partly be reversed by successful obesity treatment in childhood [ 8 ], and in adults, cognitive deficits may be improved after weight loss [ 181 , 185 ]. Regardless of mechanisms, it is of great importance to increase awareness of the association between obesity and school achievement.…”
Section: The Central Nervous System (Cns) Cognition Neuropsychology A...mentioning
confidence: 99%